DECISION SUPPORT SYSTEM USING AHP METHOD FOR BASED VILLAGE HEAD ELECTION - Valian Yoga Pudya Ardhana; Eliyah A M Sampetoding; Anarsya Sarundaitan; Hoxy R Talua (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2022)
The Village Head Election System so far has not been accurate, causing the elected village head candidates to not meet the expectations of the community. This study aims to design a decision support system (DSS) to select a web-based village head that calculates the criteria elements and alternatives using the Analytical Hierarchy Process (AHP) method. The system that is built is only up to the design of the system interface. The results of the study determined 5 elements of the criteria that the community wanted and 4 alternative elements as sample samples for prospective village heads. The criteria and alternative elements that have a consistency ratio (CR) value of <10% can be used in the designed DSS. This web-based Village head election DSS design provides information on a list of criteria and names of Village Head candidates that can be chosen by the community. Besides, it can display the results of AHP calculations.